2019
DOI: 10.1038/s41598-019-50470-z
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus D68 Subclade B3 Circulation in Senegal, 2016: Detection from Influenza-like Illness and Acute Flaccid Paralysis Surveillance

Abstract: Following the 2014 outbreak, active surveillance of the EV-D68 has been implemented in many countries worldwide. Despite subsequent EV-D68 outbreaks (2014 and 2016) reported in many areas, EV-D68 circulation remains largely unexplored in Africa except in Senegal, where low levels of EV-D68 circulation were first noted during the 2014 outbreak. Here we investigate subsequent epidemiology of EV-D68 in Senegal from June to September 2016 by screening respiratory specimens from ILI and stool from AFP surveillance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 38 publications
2
21
1
Order By: Relevance
“…Most cases (10/16) in West Africa in 2016 were detected during July (Figure 1), similar to the seasonality that has been observed in several other countries, including the United States (12), the Netherlands (13), and Senegal (3). Most EV-D68-positive patients (64.3%) were children <5 years old, consistent with our previous report from Senegal (2,3). BLAST analysis (https:// blast.ncbi.nlm.nih.gov/Blast.cgi) showed that all sequenced EV-D68 strains shared >98% homology with strains detected in Spain, Sweden, Germany, Japan, and China.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Most cases (10/16) in West Africa in 2016 were detected during July (Figure 1), similar to the seasonality that has been observed in several other countries, including the United States (12), the Netherlands (13), and Senegal (3). Most EV-D68-positive patients (64.3%) were children <5 years old, consistent with our previous report from Senegal (2,3). BLAST analysis (https:// blast.ncbi.nlm.nih.gov/Blast.cgi) showed that all sequenced EV-D68 strains shared >98% homology with strains detected in Spain, Sweden, Germany, Japan, and China.…”
supporting
confidence: 90%
“…After RNA extraction, we screened all samples for EV-D68 by real time reverse transcription PCR as described elsewhere (2). For molecular characterization, the viral protein 1 region was amplified by a nested PCR and sequenced as described elsewhere (2). The alignment and phylogenic analyses of sequences obtained after cleaning were performed using MEGA 7.0 software (https://www.…”
mentioning
confidence: 99%
“…EV-D68 emerged from the United States in 2014 showing varying clinical manifestations such as SARI, acute flaccid myelitis (AFM) and acute flaccid paralysis (AFP) [5,6]. China (2009China ( -2014 and Senegal (2016) reported EV-D68 associated SARI cases mainly in children [7][8][9]. As per the recent classification, EV-D68 has four clades namely A, B, C and D. Clade B is subclassified into B1, B2 and B3 while D1, D2 and D3 are the subclades of clade D [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As per the recent classification, EV-D68 has four clades namely A, B, C and D. Clade B is subclassified into B1, B2 and B3 while D1, D2 and D3 are the subclades of clade D [10,11]. The emerging EV-D68 strain circulating in recent years was subclade B3, and most of the cases were reported from the United States, Netherlands, Sweden, China and Senegal [9,[11][12][13][14]. Senegal had few cases in 2014 and followed by an outbreak in 2016 by novel subclade B3 in patients with influenza-like illness (ILI) and AFP [9,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation